Service-Oriented and Cloud Computing 5th IFIP WG 2.14 European Conference, ESOCC 2016, Vienna, Austria, September 5-7, 2016, Proceedings - Aiello, Marco; Johnsen, Einar Broch; Dustdar, Schahram; Georgievski, Ilche (Programming and Software Engineering,, 2016)
This book constitutes the refereed proceedings of the 5th European Conference on Service-Oriented and Cloud Computing, ESOCC 2016, held in Vienna, Austria, in September 2016. The 16 full papers presented were carefully reviewed and selected from 33 submissions. The papers are organized in topical sections on policies and performance, adaptation, SLA-aware services, job placement, compositionality, and fault tolerance.